Personality traits and diabetes incidence among postmenopausal women. Issue 6 (June 2019) - Luo, Juhua; Manson, JoAnn E.; Weitlauf, Julie C.; Shadyab, Aladdin H.; Rapp, Stephen R.; Garcia, Lorena; Jonasson, Junmei M.; Tindle, Hilary A.; Nassir, Rami; Wactawski-Wende, Jean; Hendryx, Michael
Abstract: Objective: We examined whether personality traits, including optimism, ambivalence over emotional expressiveness, negative emotional expressiveness, and hostility, were associated with risk of developing type 2 diabetes (hereafter diabetes) among postmenopausal women. Methods: A total of 139, 924 postmenopausal women without diabetes at baseline (between 1993 and 1998) aged 50 to 79 years from the Women's Health Initiative were prospectively followed for a mean of 14 (range 0.1-23) years. Multivariable Cox proportional hazards regression models were used to assess associations between personality traits and diabetes incidence adjusting for common demographic factors, health behaviors, and depressive symptoms. Personality traits were gathered at baseline using questionnaires. Diabetes during follow-up was assessed via self-report of physician-diagnosed treated diabetes. Results: There were 19, 240 cases of diabetes during follow-up. Compared with women in the lowest quartile of optimism (least optimistic), women in the highest quartile (most optimistic) had 12% (hazard ratio [HR], 0.88; 95% confidence interval [CI]: 0.84-0.92) lower risk of incident diabetes. Compared with women in the lowest quartile for negative emotional expressiveness or hostility, women in the highest quartile had 9% (HR, 1.09; 95% CI: 1.05-1.14) and 17% (HR, 1.17; 95% CI: 1.12-1.23) higher risk of diabetes, respectively. The association of hostility with risk of diabetes was stronger among nonobese than obese women. Conclusions: Low optimism and high NEE and hostility were associated with increased risk of incident diabetes among postmenopausal women independent of major health behaviors and depressive symptoms. In addition to efforts to promote healthy behaviors, women's personality traits should be considered to guide clinical or programmatic intervention strategies in diabetes prevention. Abstract : Supplemental Digital Content is available in the text